2011
DOI: 10.1016/j.schres.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic symptoms in young adults exposed to childhood trauma—A 20year follow-up study

Abstract: Childhood adversity has been shown to increase the risk of psychotic symptoms in adult life.However, there are no previous studies looking at the association between experiencing a natural disaster during childhood and the development of psychotic symptoms in young adulthood.Eight hundred and six bushfire-exposed children and 725 control children were evaluated following the 1983 South Australian bushfires. Five hundred and twenty nine (65.6%) of the bushfire group and 464 (64%) controls participated in a foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 44 publications
(43 reference statements)
2
36
0
Order By: Relevance
“…We found that losses and general traumatic events were not associated with any of the symptom domains. This resonates with studies in which experiencing the death of a close person [17], being exposed to a natural disaster [56], and having a serious accident [16] showed either weak or no association with psychosis phenotypes. Collectively, the findings indicate that maltreatment (either by commission or omission) and victimization perpetrated by same-age peers are directly linked to the real-life expression of symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…We found that losses and general traumatic events were not associated with any of the symptom domains. This resonates with studies in which experiencing the death of a close person [17], being exposed to a natural disaster [56], and having a serious accident [16] showed either weak or no association with psychosis phenotypes. Collectively, the findings indicate that maltreatment (either by commission or omission) and victimization perpetrated by same-age peers are directly linked to the real-life expression of symptoms.…”
Section: Discussionsupporting
confidence: 64%
“…Taken together, these results suggest that disrupted care in childhood is associated with HPA axis dysfunction and hyper-reactivity of the dopamine system. Pathological effects of stress on the hippocampus may be related to an increase in cortisol and a decrease in brain-derived neurotrophic factor (BDNF) (Bremner, 2005 ;Galletly et al 2011). Such hippocampal abnormalities, HPA axis disruptions and low levels of BNDF have also been described in schizophrenia, which might suggest that trauma increases the risk of psychosis in vulnerable individuals by altering brain structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, individuals with psychotic experiences have been shown to have significantly more exposure to childhood trauma (Arseneault et al, 2011;Fisher et al, 2012;Freeman and Fowler, 2009;Galletly et al, 2011;Janssen et al, 2004;Kelleher et al, 2013c;Saha et al, 2011b;Scott et al, 2007;Wigman et al, 2012b), something that might also contribute to long term dysfunction.…”
Section: Introductionmentioning
confidence: 99%